Pengaruh Harga dan Kualitas Produk terhadap Minat Beli Produk Yamaha N-Max (Studi : Yamaha Istana Motor Kuningan) - Mohamad Ilham Nurul Kamalin; Palupi Permata Rahmi, S.P., M.Si; Dr. Erna Herlinawati, S.E., M.Si (JUDICIOUS, 2023)
In the past, motorcycles were included in secondary goods, but in the present era, motorcycles are included in primary goods. This is because motorbikes are a necessity that must be met and must be owned by every individual. Primary needs are the basic needs needed by humans. While the secondary needs are the needs to complement the primary needs themselves. Tertiary needs in general are needs that are fulfilled to express the social status of the individual. This study aims to determine the effect of price and product quality on buying interest in Yamaha N-Max products at Yamaha Istana Motor Kuningan. The population in this study is infinite and 96 respondents as a sample using Non-Probability Sampling with Purposive Sampling technique. The analysis used includes validity test, reliability test, classical assumption test, multiple regression analysis, correlation coefficient, coefficient of determination and hypothesis testing. The results of the descriptive analysis show that the purchase intention is not good, the price is not good, and the quality of the product is considered not good. Based on the results of partial hypothesis testing (t test) shows that price has an effect on buying interest, product quality also has a partial effect on buying interest. The contribution of the variable Price and Product Quality is 39.3% and 17.3% and the remaining 43.4% is influenced by other factors. Simultaneously Price and Product Quality influence Purchasing Decisions, have a strong relationship and contribute 77.8%.